Pendampingan Penerapan Bauran Promosi Pada PT. Wan Teknologi Internasional. - Fahreza, Muhammad Difa; Nurendah, Yulia; Morita, Morita (Jurnal Abdimas Dedikasi Kesatuan, 2025)
Indonesia is a very potential market. Data from the Ministry of Communication and Information stated that the number of internet users is 112.6 million people, and most of them are aged 17-23 years. This shows that the majority of the productive age population in Indonesia are internet users. The purpose of this paper is to find out: 1) How is the implementation of the promotional mix at PT. Wan Teknologi Internasional; 2) What obstacles are faced in implementing the promotional mix; 3) How to overcome obstacles in implementing the promotional mix. The results of this discussion are: 1) The promotional mix carried out is advertising by advertising on the website, sales promotion by giving discounts, direct marketing by sending emails to the company, word of mouth by creating positive word of mouth, interactive marketing by using social media and websites as a medium of interaction with customers, events and sponsorships by participating in exhibitions and product launching events; 2) Constraints in implementing the promotional mix are: advertising does not run smoothly, difficulty in determining the time of implementation and duration of the promo, monotonous mailing format, difficulty controlling the effectiveness of word of mouth, brand awareness and company image have not been optimally formed, limited content ideas; 3) Solutions to overcome obstacles in the company, namely increasing creativity in the types of advertisements displayed, formulating promotions to be released and determining the duration based on discussions between related divisions, increasing creativity in the format of emails sent, distributing questionnaires related to product knowledge, increasing consumer involvement in content creation so that the content produced is content that is needed by consumers and can increase consumer curiosity regarding the services offered, becoming a sponsor and participating in events related to and in line with the company's services. Keywords: Promotion Mix, Technology